First person - Sarah Colijn (The Company of Biologists, 2020)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms (DMM), helping early-career researchers promote themselves alongside their papers. Sarah Colijn is first author on 'Cell-specific and athero-protective roles for RIPK3 in a murine model of atherosclerosis', published in DMM. Sarah conducted the research described in this article while a graduate student in Courtney Griffin's lab at Oklahoma Medical Research Foundation, Oklahoma City, OK, USA. She is now a Postdoctoral Research Associate in the lab of Amber Stratman at Washington University in St. Louis, School of Medicine, St. Louis, MO, USA, investigating how the cardiovascular system develops during embryogenesis in both physiological and pathological scenarios.